(untitled) (Al-Mansour Journal, 2022)
The problem of the finance and administrative corruption is regarded as one of the revealing problems in the contemporary life and happening in more terms that have social, psychic and ethic dimensions in any society of the world societies. This problem considers as a challenge to the law force, crime affected human honesty and social structure values as well as its impact on many political systems. This problem with its negative reverses on human psychological condition became as a problem demands field therapy, diagnoses reasons and the administrative, economic, ethic and social interventions which stand behind its happening. To avoid and prevent this problem at this time is more difficult, unless all the authorities and organizations of state, civil social, mass media and legislative board take its responsibility to prevent it as much as they can. The legal and control legislations prevent and forbid the misuse of authority or stealing public finance or took any kinds of bribe. But this problem is still going on in the society and its all organizations during (92) years of the Iraqi’s government life since the fetal stage of the state until now however it is going on towards diffusion and increase